MEASURING VEHICLE SAFE DISTANCE USING DEEP LEARNING METHODS ON SMARTPHONE DEVICES - Hidayat, Rachmat; Insani, Asep; Khusni, Uus; Hidayat, Asep Rahmat (Instrumentasi, 2024)
Maintaining a safe driving distance is an essential part of road safety. Innovations in technology, such as cameras and sensors, assist in calculating vehicle distances but come with limitations like inaccurate results and high computational demands. This research aims to develop a deep learning algorithm that helps drivers maintain a safe distance and enhance safety. Our study found that the Inception V3+DBND method allows for efficient real-time vehicle distance estimation using a smartphone camera, offering an optimal distance prediction accuracy of 97.20%. The research findings provide a practical and effective solution for measuring safe vehicle distances.